2007
DOI: 10.1158/0008-5472.can-07-1166
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the Proteasome Suppress Homologous DNA Recombination in Mammalian Cells

Abstract: Proteasome inhibitors are novel antitumor agents against multiple myeloma and other malignancies. Despite the increasing clinical application, the molecular basis of their antitumor effect has been poorly understood due to the involvement of the ubiquitin-proteasome pathway in multiple cellular metabolisms. Here, we show that treatment of cells with proteasome inhibitors has no significant effect on nonhomologous end joining but suppresses homologous recombination (HR), which plays a key role in DNA doublestra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
72
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 48 publications
10
72
1
1
Order By: Relevance
“…Proteasome function has been linked to the DDR previously by studies investigating the effects of proteasome inhibitors on IRIF and DNA repair by HR (Jacquemont and Taniguchi 2007;Murakawa et al 2007). Furthermore, a previous study reported enhanced ubiquitylation of MDC1 on chromatin following IR, linking this to proteasome-mediated disassembly of MDC1 and gH2AX foci, although the ubiquitin E3 ligases remained unknown (Shi et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteasome function has been linked to the DDR previously by studies investigating the effects of proteasome inhibitors on IRIF and DNA repair by HR (Jacquemont and Taniguchi 2007;Murakawa et al 2007). Furthermore, a previous study reported enhanced ubiquitylation of MDC1 on chromatin following IR, linking this to proteasome-mediated disassembly of MDC1 and gH2AX foci, although the ubiquitin E3 ligases remained unknown (Shi et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…While the ubiquitin-proteasome system (UPS) was originally described as the main protein turnover/ degradation machinery of eukaryotic cells, it is now evident that it is also a major nondegradative regulator of various cellular processes, including the DDR (Kirkin and Dikic 2007;Bergink and Jentsch 2009;Motegi et al 2009;Al-Hakim et al 2010). Furthermore, it has been shown that proteasomes accumulate on damaged chromatin, suggesting that they may promote DDR signaling as well as DDR-dependent protein turnover and HR (Ustrell et al 2002;Blickwedehl et al 2007;Jacquemont and Taniguchi 2007;Murakawa et al 2007;Shi et al 2008;Motegi et al 2009;Al-Hakim et al 2010;BenAroya et al 2010;Levy-Barda et al 2011). The kinetics and mechanisms governing proteasome accumulation at DNA damage regions and the functions and targets of proteasomes at such sites, however, remain largely obscure.…”
mentioning
confidence: 99%
“…2 A and B), indicating that each is simultaneously present at many of the same DSB regions throughout much of the DNA damage response. Both ␥H2AX ubiquitination and DSB targeting of several repair proteins are strongly reduced at 30 min following administration of the proteasome inhibitor MG132 (7,8,26,27). Proteasome inhibition reduces nuclear ubiquitin concentrations by preventing degradation of poly-ubiquitinated proteins in the cytosol and regeneration of free ubiquitin pools.…”
Section: Rap80-brcc36 Knockdown Restores Dsb-associated Ubiquitinationmentioning
confidence: 99%
“…Polyubiquitylation is maintained at high levels in unrepairable IRIF (Fig. 1C), and pretreatment of cells with the polyubiquitylation inhibitor MG132 (Mailand et al, 2007;Murakawa et al, 2007;Shao et al, 2009) results in the formation of IRIF that lacks 53BP1 immediately after irradiation (Fig. 4A).…”
Section: Persistent Accumulation Of Foci Components At Unrepairable Dsbsmentioning
confidence: 99%